PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS AUGUMENTED REALITY MENGGUNAKAN MODEL 4D PADA PEMBELAJARAN DESAIN ANIMASI - Fikriah Fikriah; Alimuddin Alimuddin; Nurlina Syahrir (JURNAL IMAJINASI, 2025)
This research aims to develop augmented reality (AR)-based learning media in the form of Student Worksheets (LKPD) in class IX animation design subjects at Telkom Makassar Middle School. This research uses R&D research with a 4D development model, namely Define, Design, Develop, and Disseminate to produce products that are valid, practical, and effective. The Define stage identifies student needs and challenges in learning animation design. The Design stage focuses on designing LKPD with the integration of AR technology with the hope of facilitating interactive learning and building students' learning independence. The Develop Phase conducts AR LKPD trials to ensure the validity, practicality and effectiveness of the product. The Disseminate stage involves distributing the product to teachers and students as well as holding an exhibition of work and evaluating its effectiveness. The research results show that the AR-based LKPD development is valid for use, verified through consultation with media experts and material experts with a total average score of 3.46. This product is also considered very practical because based on the responses of teachers and students, this media is able to facilitate the learning needs of students with various learning styles, increasing learning independence with an average score for teachers of 3.65 and students of 3.89. Effectiveness analysis shows a significant increase in students' understanding, enthusiasm and active involvement in the learning process after using this media. Overall research results show that augmented reality-based learning media in class IX animation design subjects at Telkom Makassar Middle School is very suitable for use, contributing to improving the quality of independent, creative and responsible learning. Keywords: learning media; augmented reality; animation; independent learning.